2015
DOI: 10.1177/1545968315613864
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex Activation While Walking Under Dual-Task Conditions in Stroke

Abstract: Background Walking while performing another task (eg, talking) is challenging for many stroke survivors, yet its neural basis are not fully understood. Objective To investigate prefrontal cortex activation and its relationship to gait measures while walking under single-task (ST) and dual-task (DT) conditions (ie, walking while simultaneously performing a cognitive task) in stroke survivors. Methods We acquired near-infrared spectroscopy (NIRS) data from the prefrontal cortex during treadmill walking in ST and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(155 citation statements)
references
References 33 publications
1
151
2
1
Order By: Relevance
“…Using a verbal fluency task, Clark et al (2014b) found an increase in prefrontal cortex activation compared to single-task walking. In a walking while counting dual-task condition, Al-Yahya et al (2016) found increased activation of the prefrontal cortex compared to single task walking in older adults with chronic stroke. Lu et al (2015) found increased activation of the left prefrontal cortex, supplementary motor area, and premotor cortex during walking while subtracting conditions and that increased premotor cortex and supplementary motor area activation were correlated with declines in gait performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a verbal fluency task, Clark et al (2014b) found an increase in prefrontal cortex activation compared to single-task walking. In a walking while counting dual-task condition, Al-Yahya et al (2016) found increased activation of the prefrontal cortex compared to single task walking in older adults with chronic stroke. Lu et al (2015) found increased activation of the left prefrontal cortex, supplementary motor area, and premotor cortex during walking while subtracting conditions and that increased premotor cortex and supplementary motor area activation were correlated with declines in gait performance.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies found an increase in activation in dual-task conditions (Holtzer et al, 2011; Doi et al, 2013; Clark et al, 2014b; Al-Yahya et al, 2016), while others found a decrease (Shimada et al, 2013; Beurskens et al, 2014; Lin and Lin, 2016). In addition, although aging negatively affects balance control, Takeuchi et al (2016) did not find a difference in prefrontal cortex activation between young and older adults while playing a game and walking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prefrontal activation increased more in dual-task condition than normal gait in nondemented elderly subjects and larger prefrontal activation correlated with larger stride length and better cognitive performance. 32 Al-Yahya et al 33 have also reported that the prefrontal activity was more prominent in dual-task walking compared with single-task walking in both healthy subjects and patients with stroke. These findings suggested that the PFC is involved in the allocation of attentional resources during dual-task walking situations.…”
Section: Neural Mechanism For Gait Controlmentioning
confidence: 94%
“…It had also been reported that dual-task can activate the brain more significantly, compared to single-task (a single task such as exercise only or learning only), and the activation of prefrontal cortex had been verified [7,8].…”
Section: Introductionmentioning
confidence: 94%